Written feedback provided by first-year engineering students, undergraduate teaching assistants, and educators on design project work. (4th March 2019) - Marbouti, Farshid; Mendoza-Garcia, John; Diefes-Dux, Heidi A.; Cardella, Monica E.
ABSTRACT: Feedback is an important part of design education. To better understand how feedback is provided to students on their engineering design work, we characterised and compared first-year engineering students', undergraduate teaching assistants', and educators' written feedback on sample student design work. We created a coding scheme including two domains: Substance and Focus of feedback. Educators made more and longer comments than undergraduate teaching assistants, and undergraduate teaching assistants made more and longer comments than first-year students. The first-year students focused on giving specific directions in their feedback while educators and undergraduate teaching assistants asked thought-provoking questions. Students tended to make more comments about the ways that their peers had communicated their design work while educators and undergraduate teaching assistants made more comments about the design ideas presented in the sample work. This study offers implications for practice for supporting educators, undergraduate teaching assistants, and first-year engineering students to be able to provide feedback on design work.